2008
DOI: 10.1177/0734016808324245
|View full text |Cite
|
Sign up to set email alerts
|

A Commentary on Age Segregation for Older Prisoners

Abstract: The growing number of older prisoners in state and federal prisons has fostered an important discussion in literature regarding the potential benefits of age-segregated living arrangements for older inmates. This article begins with a brief review of the reasons for America's aging prison population. Thereafter, it uses a multidisciplinary literature review to clarify a 4-point rationale for age-segregated prisons: (a) cost savings via centralized health care for older prisoners; (b) the reduction of civil lia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…In contrast to other studies, the present study found that violence against older prisoners did not appear to be a critical reason in support of segregated living situations. Victimisation of older prisoners who are deemed more vulnerable has been one of the key reasons put forth for segregated prisons (Adams 1995; Kerbs and Jolley 2007, 2009; Trotter and Baidawi 2015). There could be several reasons for the lack of support for this concern in our sample, including the prison culture and population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to other studies, the present study found that violence against older prisoners did not appear to be a critical reason in support of segregated living situations. Victimisation of older prisoners who are deemed more vulnerable has been one of the key reasons put forth for segregated prisons (Adams 1995; Kerbs and Jolley 2007, 2009; Trotter and Baidawi 2015). There could be several reasons for the lack of support for this concern in our sample, including the prison culture and population.…”
Section: Discussionmentioning
confidence: 99%
“…Similar arrangements are also available in the United Kingdom (Howse 2003) and in Switzerland, two prison facilities have a geriatric wing. The debate on age-segregation within prisons, not surprisingly, is US dominated (Aday 2003; Kerbs and Jolley 2009; Kerbs, Jolley and Kanaboshi 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors contribute to explaining why health care utilization has been found to be greater in prison than the general population [ 13 – 19 ]. Furthermore, developed countries are witnessing an increase in the share of elderly prisoners [ 20 , 21 ], which stems from harsher sentencing patterns with longer incarceration times [ 22 , 23 ]. Older individuals in prison naturally have a higher prevalence of chronic health conditions, serious life-limiting illnesses and comorbidity rates [ 8 , 11 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another key legal dilemma with regard to the appropriate legal policy toward older prisoners is whether they should be integrated or segregated from the general prison population (Kerbs & Jolley, 2009). If viewed as weak and unable to protect themselves from younger and more dangerous criminals, then segregating older prisoners makes sense (Aday & Krabill, 2006;(Stojkovic, 2007).…”
Section: Segregation or Integrationmentioning
confidence: 99%